Rhetorical move-step analysis of argumentative essays by Chinese EFL undergraduate students - Liu, Hongjian; Ismail, Lilliati; Ahmad, Norhakimah Khaiessa (Academy Publication, 2024)
Rhetorical move-step analysis, an analytical approach within discourse analysis, is commonly employed to scrutinize the rhetorical structures inherent in various community genre practices. This method has also been extensively applied in academic and professional writing, particularly in published research articles and doctoral dissertations. However, little research has investigated the rhetorical move-step structures evident in argumentative writing by Chinese undergraduate students. Therefore, this study explores the rhetorical move-step structure of argumentative essays in Chinese EFL contexts. A corpus comprising 30 argumentative essays authored by undergraduate students at a Chinese university was assembled for analysis. The move-step structure of the data was analyzed using Hyland’s (1990) analytical framework. The results indicated that most students utilized Hyland’s model in crafting their argumentative essays. Additionally, the findings revealed that the argumentative essays by Chinese undergraduates adhered to a structure consisting of five obligatory moves, three conventional moves, one optional move, and multiple obligatory, conventional, and optional steps beyond the established analytical framework. These findings’ implications extend to pedagogical practices and further research in the domain of EFL students’ academic writing.